Caesarean delivery through deliberate posterior hysterotomy in irriducible uterine torsion: case report - De Ioris, A.; Pezzuto, C.; Nardelli et al., G.B. (Acta Biomedica Atenei Parmensis, 2010)
Gravid uterus rotation is a normal finding in the third trimester of pregnancy. However, a rotation greater than 45º around the longitudinal axis of the uterus – uterine torsion – is a rare pathological condition in the obstetrical practice. We reporte the case of 180° torsion of a myomatous uterus at preterm in which the foetus, in breech presentation, was delivered through a deliberate posterior hysterotomy. An emergency caesarean section was arranged after prolonged foetal bradycardia. Uterine torsion treatment depends on when the torsion occurs during the pregnancy. However, laparotomy is imperative in all cases. When derotation of the uterus is not possible, a transverse incision in the lower posterior uterine segment, if feasible, is a safe choice.